Role of depression, anxiety and stress in patients with oral lichen planus: A pilot study - Chaithra Kalkur; Atul Prahlad Sattur; Kruthika Satyabodh Guttal (Wolters Kluwer Medknow Publications, 2015)
Context: Lichen planus is a psychosomatic disease. Higher frequency of psychiatric symptoms, poor quality of life, higher level of anxiety and neuroendocrine and immune dysregulations, all these factors, will enhance the exacerbation of the disease. Aims: The present study was to assess depression, anxiety and stress levels in patients with oral lichen planus. Methods: The psychometric evaluation using the Depression Anxiety Stress Scale (DASS)-42 questionnaire was carried out, by the same investigator on all members of group 1 (Oral Lichen Planus) and group 2 (Control). DASS-42 questionnaire consists of 42 symptoms divided into three subscales of 14 items: Depression scale, anxiety scale, and stress scale. Statistical Analysis Used: The Student t test was used to determine statistical difference for both the groups and to evaluate for significant relationships among variables. Results: Psychological assessment using DASS-42 reveals lichen planus patients showed higher frequency of psychiatric co morbidities like depression, anxiety and stress compared to control group. Conclusions: This study has provided evidence that the DASS-42 questionnaire is internally consistent and valid measures of depression, anxiety, and stress. Psychiatric evaluation can be considered for patients with oral lichen planus with routine treatment protocols are recommended. DASS-42 Questionnaire can also be used to determine the level of anxiety, stress and depression in diseases of the oral mucosa like recurrent apthous stomatitis, burning mouth syndrome and TMD disorders.